A pollution-resistant composite membrane and process optimization method thereof

CN122912692APending Publication Date: 2026-10-16DALTON MEMBRANE TECH (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611251037.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]上述传统优化方式虽然能够在一定程度上改善膜性能,但无法系统性地评估多个工艺参数对不同性能指标的影响

Benefits of technology

[0019]To address the problems described in the background section, this invention first identifies the target application scenario and determines the composite membrane fabrication system and basic composite membrane materials based on the target application scenario. The composite membrane fabrication system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, an organic solvent, polyetherimide, graphene oxide, and carbon nanotubes. This invention considers the differences in membrane performance requirements across different application scenarios. Using uniform materials and processes would be difficult to adapt to specific working conditions. Therefore, by clarifying the preparation direction through the target application scenario, a basis is provided for the targeted setting of subsequent process parameters. Secondly, this invention sets k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic materials of the composite membrane, k spinning solutions and k modification solutions are prepared. It can be seen that this invention takes into account the problem that traditional single-factor experiments are inefficient and difficult to cover the space of multiple parameter combinations. Therefore, through the parallel design of multiple process parameter groups, the simultaneous evaluation of multiple formulations and multiple process conditions is achieved. Then, the present invention performs the following operations on each of the k base membranes: using the base membrane, the spinning solution and the modifying solution are extracted from k sets of spinning solutions and k sets of modifying solutions, respectively, and the base membrane is pretreated to obtain a standard base membrane. According to the composite membrane fabrication system, the spinning solution, and the modifying solution, the standard base membrane is sequentially spun, crosslinked, coated, and cured to obtain a standard composite membrane. It is evident that the present invention addresses the problem of isolated testing of various factors and difficulty in systematic comparison in traditional optimization methods. Therefore, through the one-to-one correspondence between the base membrane, spinning solution, and modifying solution, parallel preparation and systematic processing of multiple sets of experiments are achieved. Next, the present invention conducts antifouling performance tests on the standard composite membranes to obtain an antifouling performance dataset. The antifouling performance datasets are then summarized to obtain k antifouling performance datasets. It is evident that the present invention addresses the problem that traditional methods evaluate membrane performance using only a single index, which cannot comprehensively reflect antifouling ability. Therefore, through multi-dimensional antifouling performance testing, complete performance indicators for each membrane sample are obtained. Subsequently, this invention selects n qualified antifouling datasets from k antifouling performance datasets, where n is no greater than k. It is evident that this invention considers that the performance of membranes prepared by some process combinations may not meet the basic application requirements, and directly including them in the evaluation would affect the accuracy of the selection. Therefore, unqualified samples are eliminated through threshold screening to ensure that all data participating in the comprehensive evaluation meet the basic performance standards.Finally, this invention calculates the comprehensive evaluation score for each of the n qualified antifouling datasets, obtaining n comprehensive evaluation scores. The highest comprehensive evaluation score is selected from these n scores, and the standard composite membrane corresponding to this highest score is chosen as the antifouling composite membrane. This optimizes the antifouling composite membrane process. It is evident that this invention addresses the subjectivity and inefficiency of manually comparing multi-dimensional performance data based on experience. By using weighted comprehensive evaluation, multi-dimensional indicators are quantified into a single score, achieving objective and efficient optimal decision-making. Therefore, this invention can efficiently optimize the antifouling composite membrane preparation process, improve the antifouling performance and preparation efficiency of membrane products, and adapt to the needs of different water treatment application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912692A_ABST
    Figure CN122912692A_ABST
Patent Text Reader

Abstract

The application relates to the field of composite separation membrane preparation, in particular to an anti-pollution composite membrane and a process optimization method thereof, which comprises the following steps: confirming a target application scene, determining a composite membrane manufacturing system and composite membrane basic materials, setting k process parameter groups, preparing k groups of spinning liquids and k groups of modification liquids according to the k process parameter groups and the composite membrane basic materials, pretreating a base film to obtain a standard composite membrane, testing the anti-pollution performance of the standard composite membrane to obtain k anti-pollution performance data sets, screening n qualified anti-pollution data sets, calculating the comprehensive evaluation scores of each qualified anti-pollution data set, and taking the standard composite membrane corresponding to the maximum comprehensive evaluation score as the anti-pollution composite membrane. The application can realize efficient optimization of the anti-pollution composite membrane preparation process, improve the anti-pollution performance and preparation efficiency of the membrane product, and adapt to the requirements of different water treatment application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite separation membrane preparation, and more particularly to an antifouling composite membrane and its process optimization method. Background Technology

[0002] With the increasing scarcity of water resources and ever-increasing environmental protection requirements, membrane separation technology has been widely applied in water treatment, seawater desalination, and oil-water separation. As a core component of membrane separation systems, the antifouling performance of composite membranes directly affects operating efficiency, cleaning frequency, and service life, and is a key factor determining the feasibility of membrane technology. Therefore, how to improve the antifouling performance of composite membranes through process optimization has become a research hotspot in the preparation of composite separation membranes.

[0003] Currently, the optimization of the preparation process of antifouling composite membranes usually adopts single-factor experimental method or orthogonal experimental method, that is, changing a certain preparation parameter one by one, and determining the optimal process conditions by testing a single index such as the membrane's hydrophilicity, flux or rejection rate, based on experience or simple comparison.

[0004] While the aforementioned traditional optimization methods can improve membrane performance to some extent, they cannot systematically evaluate the impact of multiple process parameters on different performance indicators. Furthermore, existing optimization methods use only a single indicator as an evaluation criterion, lacking a comprehensive evaluation mechanism for antifouling performance, making it difficult to guarantee the overall performance of the final product in practical applications. Therefore, this invention proposes an antifouling composite membrane and its process optimization method, combining multi-parameter parallel experiments with multi-indicator comprehensive evaluation to achieve efficient and systematic optimization of the antifouling composite membrane preparation process. Summary of the Invention

[0005] This invention provides an antifouling composite membrane and its process optimization method. Its main purpose is to achieve efficient optimization of the antifouling composite membrane preparation process, improve the antifouling performance and preparation efficiency of the membrane product, and adapt to the needs of different water treatment application scenarios.

[0006] To achieve the above objectives, the present invention provides an antifouling composite membrane and its process optimization method, comprising: The target application scenario is identified, and the composite membrane manufacturing system and basic composite membrane materials are determined based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, organic solvents, polyetherimide, graphene oxide, and carbon nanotubes. Set k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, prepare k spinning solutions and k modification solutions. Perform the following operation on each of the k base films: Using the base membrane, spinning solution and modified solution were extracted from group k spinning solution and group k modified solution, respectively; The base film is pretreated to obtain a standard base film. The standard base film is then spun, crosslinked, coated and cured sequentially according to the composite film manufacturing system, spinning solution and modifying solution to obtain a standard composite film. Antifouling performance tests were conducted on standard composite membranes to obtain antifouling performance datasets. These datasets were then compiled to obtain k antifouling performance datasets. Select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k; Calculate the comprehensive evaluation score of each of the n qualified anti-fouling datasets to obtain n comprehensive evaluation scores. Select the largest comprehensive evaluation score from the n comprehensive evaluation scores and use the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-fouling composite membrane to achieve process optimization of the anti-fouling composite membrane.

[0007] Optionally, the preparation of k sets of spinning solutions and k sets of modified solutions based on k sets of process parameters and composite membrane base materials includes: Extract the process parameter sets sequentially from the k process parameter sets; Weigh out the corresponding masses of polyetherimide, organic solvent, graphene oxide, and carbon nanotubes based on the amount of polyetherimide, organic solvent, graphene oxide, and carbon nanotubes added. Polyetherimide was added to an organic solvent for degassing treatment to obtain a spinning solution; Prepare the dispersion solvent according to the solvent concentration; Graphene oxide and carbon nanotubes were added to a dispersion solvent to obtain a mixture; The mixture was subjected to fractional dispersion treatment based on the dispersion time to obtain the modified liquid; The spinning solution and the modified solution were summarized separately to obtain k groups of spinning solutions and k groups of modified solutions.

[0008] Optionally, the step of fractionating the mixture according to the dispersion time to obtain the modified liquid includes: The initial aggregate particle size and specific surface area of ​​carbon nanotubes were determined, and the dispersion difficulty coefficient was calculated based on the initial aggregate particle size and specific surface area. Set a first dispersion level threshold and a second dispersion level threshold, wherein the second dispersion level threshold is greater than the first dispersion level threshold; If the dispersion difficulty coefficient is not greater than the first dispersion level threshold, the mixture is ultrasonically dispersed using a preset first ultrasonic power according to the dispersion time to obtain dispersion No. 1. If the dispersion difficulty coefficient is greater than the second dispersion level threshold, the mixture is ultrasonically dispersed using a preset second ultrasonic power according to the dispersion time to obtain dispersion No. 2. Otherwise, the mixture is ultrasonically dispersed using a preset third ultrasonic power according to the dispersion time, and a pre-prepared dispersant is added during the ultrasonic dispersion process to obtain dispersion No. 3. The No. 1 dispersion, No. 2 dispersion, or No. 3 dispersion is used as the modifying liquid.

[0009] Optionally, the pretreatment of the base film to obtain a standard base film includes: The base film is immersed in a dispersion solvent for wetting treatment to obtain an impregnated base film; The impregnated base film was subjected to ultrasonic cleaning to obtain an ultrasonically cleaned base film. The ultrasonically cleaned base film is dried to obtain a dried base film. The dried base film was subjected to plasma surface activation treatment to obtain an activated base film; The activated base film was subjected to low-temperature plasma surface etching to obtain a standard base film.

[0010] Optionally, the plasma surface activation treatment of the dried base film to obtain an activated base film includes: The dried base film was fixed in a pre-constructed plasma processing device and subjected to vacuum treatment to obtain a processing chamber; Multiple activation times are set, and the activation time is extracted sequentially from these multiple activation times. Pre-confirmed argon gas is introduced into the processing chamber according to the activation time to obtain the activation environment. The dried base film was subjected to plasma surface activation treatment in an activation environment to obtain an activated base film; The surface contact angle of the activated base film was tested to obtain the contact angle parameters after activation. The surface free energy of the activated substrate film is calculated based on the contact angle parameters after activation, and the calculation formula is shown below:

[0011] in, This represents the surface free energy. This represents the preset liquid surface tension. This represents the activated contact angle parameter. This represents the preset cosine function; If the surface free energy is not less than the preset surface free energy threshold, then the activated base film is used as the activated base film.

[0012] Optionally, the standard composite membrane is obtained by sequentially spinning, crosslinking, coating, and curing the standard base membrane using a composite membrane fabrication system, spinning solution, and modifying solution, including: A standard base film is fixed onto a receiving roller to obtain a fixed base; The spinning solution is injected into a syringe, and the fixed substrate is electrospinned using the syringe to obtain a spun composite film. The spun composite membrane is placed in a crosslinking device, and pre-prepared ethylenediamine vapor is introduced into the crosslinking device for crosslinking treatment to obtain a crosslinked composite membrane. The cross-linked composite membrane is placed in a coating device, and the cross-linked composite membrane is filtered and coated with a modified liquid to obtain a precursor membrane. The precursor film is placed in a curing device for segmented curing to obtain a standard composite film.

[0013] Optionally, the step of placing the precursor film in a curing apparatus for segmented curing to obtain a standard composite film includes: Measure the initial dimensional parameters of the precursor membrane, including the initial length and initial width; Set multiple curing conditions, each of which includes curing temperature and curing time; Curing conditions are extracted sequentially from multiple sets of curing conditions. The curing device is initialized using the curing temperature and curing time in the curing conditions. The precursor film is then cured using the initialized curing device to obtain the cured film. Measure the cured dimensional parameters of the film, including the cured length and cured width. The isotropic shrinkage rate was calculated based on the initial and cured dimensional parameters, using the following formula:

[0014] in, This represents the isotropic shrinkage rate. This indicates the initial length. This indicates the length after curing. This represents the initial width. Indicates the width after curing; When the isotropic shrinkage rate is not greater than the preset shrinkage rate threshold, the cured film is used as the standard composite film.

[0015] Optionally, the step of selecting n qualified anti-pollution datasets from k anti-pollution performance datasets includes: Anti-fouling performance datasets are extracted sequentially from k anti-fouling performance datasets, wherein the anti-fouling performance datasets include: static water contact angle parameters, pure water flux parameters, flux decay rate parameters, flux recovery rate parameters, and oil-water retention rate parameters. Obtain a set of antifouling performance thresholds, which includes: static water contact angle threshold, pure water flux threshold, flux decay rate threshold, flux recovery rate threshold, and oil-water retention rate threshold. If the static water contact angle parameter is not greater than the static water contact angle threshold, the pure water flux parameter is not less than the pure water flux threshold, the flux decay rate parameter is not greater than the flux decay rate threshold, the flux recovery rate parameter is not less than the flux recovery rate threshold, and the oil-water retention rate parameter is not less than the oil-water retention rate threshold, then the corresponding anti-fouling performance dataset is determined to be a qualified anti-fouling dataset. By summarizing the qualified anti-fouling datasets, n qualified anti-fouling datasets are obtained.

[0016] To achieve the above objectives, the present invention also provides an antifouling composite membrane and a process optimization system thereof, comprising: The scenario system confirmation module is used to confirm the target application scenario and determine the composite membrane manufacturing system and the basic materials of the composite membrane based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device and a curing device, and the spinning device includes a receiving roller and a syringe. The basic materials of the composite membrane include k base films, organic solvents, polyetherimide, graphene oxide and carbon nanotubes. The parameter liquid preparation module is used to set k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, k spinning solutions and k modification solutions are prepared. The membrane preparation and testing module is used to perform the following operations on each of the k base membranes: using the base membrane, the spinning solution and the modifying solution are extracted from k sets of spinning solutions and k sets of modifying solutions respectively, the base membrane is pretreated to obtain a standard base membrane, the standard base membrane is sequentially spun, crosslinked, coated and cured according to the composite membrane manufacturing system, the spinning solution and the modifying solution to obtain a standard composite membrane, the antifouling performance of the standard composite membrane is tested to obtain an antifouling performance dataset, and the antifouling performance datasets are summarized to obtain k antifouling performance datasets; The comprehensive evaluation and selection module is used to select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k. It calculates the comprehensive evaluation score of each qualified anti-pollution dataset in the n qualified anti-pollution datasets to obtain n comprehensive evaluation scores. It selects the largest comprehensive evaluation score from the n comprehensive evaluation scores and uses the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-pollution composite membrane to achieve process optimization of anti-pollution composite membrane.

[0017] To address the above problems, the present invention also provides an electronic device, the electronic device comprising: Memory, storing at least one instruction; The processor executes the instructions stored in the memory to implement the antifouling composite membrane and its process optimization method described above.

[0018] To address the aforementioned problems, the present invention also provides a computer-readable storage medium storing at least one instruction, which is executed by a processor in an electronic device to implement the aforementioned antifouling composite membrane and its process optimization method.

[0019] To address the problems described in the background section, this invention first identifies the target application scenario and determines the composite membrane fabrication system and basic composite membrane materials based on the target application scenario. The composite membrane fabrication system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, an organic solvent, polyetherimide, graphene oxide, and carbon nanotubes. This invention considers the differences in membrane performance requirements across different application scenarios. Using uniform materials and processes would be difficult to adapt to specific working conditions. Therefore, by clarifying the preparation direction through the target application scenario, a basis is provided for the targeted setting of subsequent process parameters. Secondly, this invention sets k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic materials of the composite membrane, k spinning solutions and k modification solutions are prepared. It can be seen that this invention takes into account the problem that traditional single-factor experiments are inefficient and difficult to cover the space of multiple parameter combinations. Therefore, through the parallel design of multiple process parameter groups, the simultaneous evaluation of multiple formulations and multiple process conditions is achieved. Then, the present invention performs the following operations on each of the k base membranes: using the base membrane, the spinning solution and the modifying solution are extracted from k sets of spinning solutions and k sets of modifying solutions, respectively, and the base membrane is pretreated to obtain a standard base membrane. According to the composite membrane fabrication system, the spinning solution, and the modifying solution, the standard base membrane is sequentially spun, crosslinked, coated, and cured to obtain a standard composite membrane. It is evident that the present invention addresses the problem of isolated testing of various factors and difficulty in systematic comparison in traditional optimization methods. Therefore, through the one-to-one correspondence between the base membrane, spinning solution, and modifying solution, parallel preparation and systematic processing of multiple sets of experiments are achieved. Next, the present invention conducts antifouling performance tests on the standard composite membranes to obtain an antifouling performance dataset. The antifouling performance datasets are then summarized to obtain k antifouling performance datasets. It is evident that the present invention addresses the problem that traditional methods evaluate membrane performance using only a single index, which cannot comprehensively reflect antifouling ability. Therefore, through multi-dimensional antifouling performance testing, complete performance indicators for each membrane sample are obtained. Subsequently, this invention selects n qualified antifouling datasets from k antifouling performance datasets, where n is no greater than k. It is evident that this invention considers that the performance of membranes prepared by some process combinations may not meet the basic application requirements, and directly including them in the evaluation would affect the accuracy of the selection. Therefore, unqualified samples are eliminated through threshold screening to ensure that all data participating in the comprehensive evaluation meet the basic performance standards.Finally, this invention calculates the comprehensive evaluation score for each of the n qualified antifouling datasets, obtaining n comprehensive evaluation scores. The highest comprehensive evaluation score is selected from these n scores, and the standard composite membrane corresponding to this highest score is chosen as the antifouling composite membrane. This optimizes the antifouling composite membrane process. It is evident that this invention addresses the subjectivity and inefficiency of manually comparing multi-dimensional performance data based on experience. By using weighted comprehensive evaluation, multi-dimensional indicators are quantified into a single score, achieving objective and efficient optimal decision-making. Therefore, this invention can efficiently optimize the antifouling composite membrane preparation process, improve the antifouling performance and preparation efficiency of membrane products, and adapt to the needs of different water treatment application scenarios. Attached Figure Description

[0020] Figure 1 A schematic flowchart illustrating an embodiment of the antifouling composite membrane and its process optimization method provided by the present invention; Figure 2 A functional block diagram of an antifouling composite membrane and its process optimization system provided in an embodiment of the present invention; Figure 3 This is a schematic diagram of an electronic device for implementing the antifouling composite membrane and its process optimization method according to an embodiment of the present invention.

[0021] Explanation of reference numerals in the attached figures: 10. Electronic device; 11. Processor; 12. Memory; 13. Bus.

[0022] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0023] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0024] This application provides an antifouling composite membrane and a method for optimizing its process. The executing entity of the antifouling composite membrane and the method for optimizing its process includes, but is not limited to, at least one of the following electronic devices that can be configured to execute the method provided in this application: a server, a terminal, etc. In other words, the antifouling composite membrane and the method for optimizing its process can be executed by software or hardware installed on a terminal device or a server device, and the software can be a blockchain platform. The server includes, but is not limited to, a single server, a server cluster, a cloud server, or a cloud server cluster.

[0025] Reference Figure 1 The diagram shown is a schematic flow chart of an antifouling composite membrane and its process optimization method according to an embodiment of the present invention. In this embodiment, the antifouling composite membrane and its process optimization method include: S1. Confirm the target application scenario, and determine the composite membrane manufacturing system and basic composite membrane materials based on the target application scenario. The composite membrane manufacturing system includes: a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include: k base films, organic solvents, polyetherimide, graphene oxide, and carbon nanotubes.

[0026] It is understandable that the target application scenario refers to the specific working environment in which the antifouling composite membrane is expected to be used, which determines the selection of the subsequent composite membrane manufacturing system and the proportioning direction of the basic materials of the composite membrane. For example, treatment of oily wastewater, secondary effluent purification, or seawater desalination pretreatment, etc. This embodiment of the invention uses the treatment of oily wastewater as an example for illustration. The composite membrane manufacturing system is a set of equipment used to execute the entire process of antifouling composite membrane preparation, including a spinning device, a crosslinking device, a coating device, and a curing device, used to ensure that the base membrane undergoes spinning, crosslinking, coating, and curing treatments in sequence to form an antifouling composite membrane. The basic materials of the composite membrane are a collective term for all raw materials required to prepare the antifouling composite membrane, including k base membranes, organic solvents, polyetherimide, graphene oxide, and carbon nanotubes, where k is a positive integer greater than 1, and the number of base membranes is consistent with the number of subsequent process parameter sets.

[0027] It should be understood that the spinning device is a device used to form a fiber layer on the surface of a base film by electrospinning, comprising a receiving roller and a syringe. The syringe is a container for containing and quantitatively extruding the spinning solution; its front end is connected to a metal needle, and the spinning solution is stretched into fibers by a high-voltage electric field. The receiving roller is a cylindrical metal roller used to fix and rotate the base film, ensuring uniform deposition of fibers on the base film surface during spinning to form a fiber layer. The crosslinking device is a closed device for chemically crosslinking the spun composite film; ethylenediamine vapor can be introduced internally to induce a crosslinking reaction in the fiber layer, thereby improving the mechanical stability and solvent resistance of the fiber layer and forming a crosslinked layer. The coating device is used to coat the crosslinked layer with a modified solution through filtration, forming a uniform modified layer on the surface of the crosslinked layer. The curing device is used to heat-cur the precursor film, ensuring a firm bond between the modified layer and the base film and eliminating internal stress.

[0028] It should be clarified that the base membrane is an unmodified polyvinylidene fluoride (PVDF) fiber membrane, used as a support layer for the composite membrane. For example, the PVDF fiber membrane used in this embodiment has an average pore size between 0.1 μm and 0.5 μm. The organic solvent is a volatile liquid used to dissolve the polyetherimide to obtain a uniform spinning solution. For example, dimethylacetamide is used as the organic solvent. The polyetherimide is a thermoplastic polymer material with excellent mechanical properties and chemical resistance. It is used to form a fiber layer on the surface of the base membrane through electrospinning, and then crosslinked to form a crosslinked layer. Its function is to enhance the overall strength of the composite membrane and provide a good adhesion substrate for subsequent modified layers. The graphene oxide is an oxygen-containing derivative of graphene, and its surface contains hydrophilic functional groups such as hydroxyl, carboxyl, and epoxy groups. Graphene oxide and carbon nanotubes together constitute a composite modified layer, used to improve the hydrophilicity of the composite membrane surface, thereby enhancing its antifouling performance. The carbon nanotubes are hollow tubular carbon materials formed by rolling up graphene sheets. They have high specific surface area and excellent mechanical properties. The carbon nanotubes and graphene oxide are dispersed together in a dispersion solvent and then filtered and coated to form a modified layer. This modified layer is used to increase the surface roughness and negative charge of the composite film and inhibit the adhesion of pollutants through a dual mechanism of electrostatic repulsion and size exclusion.

[0029] S2. Set k process parameter groups, where each process parameter group includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, prepare k spinning solutions and k modification solutions.

[0030] It is understood that the process parameters are a set of values ​​used to control the proportions of each component and the processing conditions during the preparation of the antifouling composite membrane. The purpose of setting multiple sets of process parameters is to cover different preparation conditions so that the optimal combination can be selected later.

[0031] It should be understood that the polyetherimide addition amount is the mass value of polyetherimide in a process parameter group, in grams (g). The organic solvent amount is the volume value of organic solvent in a process parameter group, in milliliters (mL). The solvent concentration is the volume fraction of ethanol in the dispersion solvent, in percentages (%). The graphene oxide addition amount is the mass value of graphene oxide in a process parameter group, in grams (g). The carbon nanotube addition amount is the mass value of carbon nanotubes in a process parameter group, in grams (g), usually added with graphene oxide at a mass ratio of 1:1 to 3:1. The dispersion time is the duration of ultrasonic dispersion treatment, in minutes (min). For example, a process parameter group is: {10g, 100mL, 50%, 0.5g, 0.5g, 25min}, where each parameter corresponds from left to right to the polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Each process parameter group includes the above six parameters.

[0032] Specifically, the preparation of k sets of spinning solutions and k sets of modified solutions based on k sets of process parameters and composite membrane basic materials includes: Extract the process parameter sets sequentially from the k process parameter sets; Weigh out the corresponding masses of polyetherimide, organic solvent, graphene oxide, and carbon nanotubes based on the amount of polyetherimide, organic solvent, graphene oxide, and carbon nanotubes added. Polyetherimide was added to an organic solvent for degassing treatment to obtain a spinning solution; Prepare the dispersion solvent according to the solvent concentration; Graphene oxide and carbon nanotubes were added to a dispersion solvent to obtain a mixture; The mixture was subjected to fractional dispersion treatment based on the dispersion time to obtain the modified liquid; The spinning solution and the modified solution were summarized separately to obtain k groups of spinning solutions and k groups of modified solutions.

[0033] It should be clarified that the degassing treatment involves dissolving polyetherimide in an organic solvent and then removing air bubbles from the solution through standing or vacuuming. Its purpose is to prevent air bubbles from causing fiber breakage or unevenness during electrospinning. For example, in this embodiment of the invention, the degassing treatment uses a vacuum degassing method, where the organic solvent containing polyetherimide is allowed to stand for 2 hours at a pressure of -0.09 MPa. The spinning solution is a uniform, viscous liquid obtained after dissolving polyetherimide in an organic solvent and completing the degassing treatment, used for subsequent electrospinning to form the fiber layer. The dispersing solvent is a mixed solvent obtained by mixing anhydrous ethanol and deionized water according to the solvent concentration. The deionized water is pure water obtained by removing ionic impurities from water through ion exchange, used to avoid the influence of metal ions such as calcium and magnesium ions in the water on the dispersion stability of graphene oxide and carbon nanotubes, ensuring the quality of the modified solution. For example, when the solvent concentration is 50%, 500 mL of anhydrous ethanol and 500 mL of deionized water are mixed evenly to obtain a 50% (v / v) ethanol-water solution. The mixture is a suspension obtained by adding graphene oxide and carbon nanotubes to a dispersion solvent and performing preliminary stirring. At this stage, the carbon nanotubes are not fully dispersed and are in an agglomerated state. The modified liquid is a suspension of carbon nanotubes and graphene oxide uniformly dispersed after the mixture undergoes a graded dispersion treatment. It is used for subsequent filtration coating to form a composite modified layer.

[0034] Specifically, the step of fractionating the mixture according to the dispersion time to obtain the modified liquid includes: The initial aggregate particle size and specific surface area of ​​carbon nanotubes were determined, and the dispersion difficulty coefficient was calculated based on the initial aggregate particle size and specific surface area. Set a first dispersion level threshold and a second dispersion level threshold, wherein the second dispersion level threshold is greater than the first dispersion level threshold; If the dispersion difficulty coefficient is not greater than the first dispersion level threshold, the mixture is ultrasonically dispersed using a preset first ultrasonic power according to the dispersion time to obtain dispersion No. 1. If the dispersion difficulty coefficient is greater than the second dispersion level threshold, the mixture is ultrasonically dispersed using a preset second ultrasonic power according to the dispersion time to obtain dispersion No. 2. Otherwise, the mixture is ultrasonically dispersed using a preset third ultrasonic power according to the dispersion time, and a pre-prepared dispersant is added during the ultrasonic dispersion process to obtain dispersion No. 3. The No. 1 dispersion, No. 2 dispersion, or No. 3 dispersion is used as the modifying liquid.

[0035] It should be explained that the initial aggregate particle size is the equivalent diameter of the carbon nanotube aggregates in the undispersed state, measured in nanometers (nm). The initial aggregate particle size determination method is as follows: a small amount of carbon nanotube powder is dispersed in a dispersion solvent, ultrasonically treated for 30 seconds, and then measured to obtain the volume average particle size. For example, an adjustable-power ultrasonic cleaner and a laser particle size analyzer in wet mode can be used to ultrasonically treat the carbon nanotube powder and measure the particle size distribution of the carbon nanotube aggregates. 0.1g of carbon nanotube powder is weighed and added to 100mL of a 50% (v / v) ethanol aqueous solution. The mixture is ultrasonically treated at 200W power for 30 seconds to obtain the dispersion to be tested. The dispersion is injected into the wet sample cell of the laser particle size analyzer, and the particle size distribution of the carbon nanotube aggregates is measured in wet mode. The volume average particle size is calculated based on the particle size distribution, and the volume average particle size is used as the initial aggregate particle size. The measurement is repeated three times, and the average of the three measurements is taken as the final initial aggregate particle size. The specific surface area is the total surface area per unit mass of carbon nanotubes, expressed in square meters per gram. The dispersion difficulty coefficient was determined by nitrogen adsorption BET method. This dispersion difficulty coefficient is a dimensionless parameter quantifying the difficulty of dispersing carbon nanotubes. It is calculated based on the initial aggregate particle size and specific surface area. A higher dispersion difficulty coefficient indicates that the carbon nanotubes are more difficult to disperse and require more stringent dispersion conditions. The formula for calculating the dispersion difficulty coefficient is shown below:

[0036] in, This represents the dispersion difficulty coefficient. This represents the preset first weighting coefficient. The initial aggregate particle size is indicated in nanometers (nm). This indicates the preset reference agglomerate size, in nanometers (nm). This represents the preset second weighting coefficient. The specific surface area is expressed in square meters per gram. , This indicates the preset reference specific surface area, in square meters per gram. .

[0037] Understandably, the first and second weighting coefficients are dimensionless parameters used to balance the contributions of initial aggregate particle size and specific surface area to dispersion difficulty. They are set based on: determining the contribution ratio of particle size and specific surface area to dispersion difficulty through principal component analysis of multiple batches of carbon nanotube samples. For example, taking... =0.6, =0.4, and the sum of the two is 1. The reference aggregate particle size is a reference value used to normalize the initial aggregate particle size, and the unit is nanometers (nm). It is set based on: statistically analyzing the initial aggregate particle size distribution of commonly used carbon nanotube products, and taking the median as the reference value. The larger the ratio of the initial aggregate particle size to the reference aggregate particle size, the more severe the initial aggregation of carbon nanotubes, and the higher the difficulty of dispersion. The reference specific surface area is a reference value used to normalize the specific surface area, and the unit is square meters per gram. The criteria are as follows: statistically analyze the specific surface area distribution of commonly used carbon nanotube products, and take the median as the reference value. The larger the ratio of specific surface area to reference specific surface area, the higher the surface energy of the carbon nanotube, the stronger the van der Waals forces between particles, the easier it is to aggregate, and the more difficult it is to disperse.

[0038] It should be understood that the first and second dispersion level thresholds are dimensionless critical values ​​used to classify the dispersion difficulty levels. For example, taking 10 batches of carbon nanotubes from different sources and of different specifications as a sample set, and treating each batch of carbon nanotubes as a single sample, dispersion experiments are conducted on each sample. The relationship between the dispersion difficulty coefficient of each sample in the sample set and the ultrasonic power required to achieve stable dispersion is statistically analyzed. The 10 dispersion difficulty coefficients are sorted from smallest to largest, and the 7th value after sorting is taken as the first dispersion level threshold, and the 9th value after sorting is taken as the second dispersion level threshold. When the dispersion difficulty coefficient is not greater than 0.5, it indicates that the carbon nanotubes are easy to disperse; when the dispersion difficulty coefficient is greater than 1.0, it indicates that the carbon nanotubes are extremely difficult to disperse. The first, second, and third ultrasonic powers are ultrasonic output powers artificially set for different dispersion difficulty levels, and the unit is watts (W). The setup is based on preliminary experimental results. For samples with a dispersion difficulty coefficient of no more than 0.5, a 200W ultrasonic power is sufficient to achieve stable dispersion within the specified time. For samples with a dispersion difficulty coefficient greater than 1.0, a 600W ultrasonic power is required, supplemented with a dispersant. Samples in between require a 400W ultrasonic power. The ultrasonic dispersion process involves placing a container filled with the mixture in an ultrasonic water bath. The cavitation effect of ultrasound dissociates the carbon nanotube aggregates, thus uniformly dispersing the carbon nanotubes in the mixture. The ultrasonic water bath is a constant-temperature bath containing a liquid medium and equipped with an ultrasonic generator. It transmits ultrasonic energy through the water medium to the container immersed in the bath, causing cavitation in the mixture and thereby dispersing the carbon nanotubes.

[0039] It should be clarified that the No. 1, No. 2, and No. 3 dispersions correspond to three intermediate modified liquids obtained from three different fractional dispersion treatments. Specifically, the No. 1 dispersion is obtained by low-power ultrasonic treatment and is suitable for easily dispersed carbon nanotubes; the No. 2 dispersion is obtained by medium-power ultrasonic treatment and is suitable for carbon nanotubes with moderate dispersion difficulty; and the No. 3 dispersion is obtained by high-power ultrasonic treatment with the addition of a dispersant and is suitable for extremely difficult-to-disperse carbon nanotubes. The dispersant is a surfactant used to assist in the dispersion of carbon nanotubes. In this embodiment, sodium dodecylbenzenesulfonate is used, added at 5% of the carbon nanotube mass, to prevent the carbon nanotubes from re-aggregating.

[0040] S3. Using the base membrane, the spinning solution and the modified solution are extracted from the k-group spinning solution and the k-group modified solution, respectively.

[0041] It should be explained that the extraction of spinning solution and modified solution from k groups of spinning solution and k groups of modified solution respectively means: identifying the spinning solution and modified solution corresponding to the base film, and extracting the corresponding spinning solution and modified solution from k groups of spinning solution and k groups of modified solution for use in subsequent processing.

[0042] S4. Pre-treat the base film to obtain a standard base film. Then, according to the composite film manufacturing system, spinning solution and modifying solution, the standard base film is sequentially spun, cross-linked, coated and cured to obtain a standard composite film.

[0043] Understandably, the standard base film is a clean and surface-activated membrane material obtained after a complete pretreatment process. Its surface has been cleaned of impurities and active groups have been introduced to ensure the firm adhesion of subsequent functional layers, improving the overall stability of the composite membrane. It is used for subsequent spinning, crosslinking, coating, and curing processes. The standard composite membrane is a complete membrane product obtained by sequentially spinning, crosslinking, coating, and curing the standard base film. Its structure includes a base film layer, a polyetherimide crosslinking layer, and a composite modification layer, used for antifouling performance testing to screen for optimal process parameters.

[0044] Specifically, the pretreatment of the base film to obtain a standard base film includes: The base film is immersed in a dispersion solvent for wetting treatment to obtain an impregnated base film; The impregnated base film was subjected to ultrasonic cleaning to obtain an ultrasonically cleaned base film. The ultrasonically cleaned base film is dried to obtain a dried base film. The dried base film was subjected to plasma surface activation treatment to obtain an activated base film; The activated base film was subjected to low-temperature plasma surface etching to obtain a standard base film.

[0045] It should be understood that the immersion treatment involves completely immersing the base film in the dispersion solvent and allowing it to stand for a certain period of time. Its purpose is to fully wet the base film, soften its surface, and facilitate subsequent ultrasonic cleaning to remove impurities. The immersed base film is the base film after the immersion treatment, whose surface is fully wetted by the dispersion solvent. The ultrasonic cleaning treatment involves placing the immersed base film in an ultrasonic cleaning device and using the cavitation effect generated by ultrasound in the liquid to remove oil, particles, and other impurities adhering to the surface of the immersed base film. Its purpose is to improve the cleanliness of the immersed base film surface. The ultrasonically cleaned base film is the immersed base film after the ultrasonic cleaning treatment, whose surface impurities have been largely removed. The drying treatment involves placing the ultrasonically cleaned base film in a drying device and removing residual moisture and ethanol from the ultrasonically cleaned base film by heating or blowing air. Its purpose is to prevent residual solvent from affecting the subsequent plasma treatment effect. The dried base film is the ultrasonically cleaned base film after the drying treatment, whose surface is dry and clean, and is used for plasma treatment. The activated base film is a film material obtained by plasma surface activation treatment of a dried base film. Polar functional groups such as hydroxyl and carboxyl groups are introduced onto its surface, increasing its surface free energy and enhancing its adhesion to the modifying liquid during subsequent etching or coating. The low-temperature plasma surface etching treatment involves placing the activated base film in a low-temperature plasma treatment device and performing microscopic physical etching on the surface of the activated base film under low pressure using plasma generated by gas discharge. This further increases the surface roughness of the activated base film, forming micro / nano structures, thereby enhancing the bonding effect between the subsequent modifying layer and the activated base film. The difference between the low-temperature plasma surface etching treatment and the plasma surface activation treatment is that the activation treatment mainly introduces functional groups, while the etching treatment mainly changes the surface morphology.

[0046] Specifically, the plasma surface activation treatment of the dried base film to obtain an activated base film includes: The dried base film was fixed in a pre-constructed plasma processing device and subjected to vacuum treatment to obtain a processing chamber; Multiple activation times are set, and the activation time is extracted sequentially from these multiple activation times. Pre-confirmed argon gas is introduced into the processing chamber according to the activation time to obtain the activation environment. The dried base film was subjected to plasma surface activation treatment in an activation environment to obtain an activated base film; The surface contact angle of the activated base film was tested to obtain the contact angle parameters after activation. The surface free energy of the activated substrate film is calculated based on the contact angle parameters after activation, and the calculation formula is shown below:

[0047] in, This represents the surface free energy. This indicates the preset liquid surface tension. This represents the activated contact angle parameter. This represents the preset cosine function; If the surface free energy is not less than the preset surface free energy threshold, then the activated base film is used as the activated base film.

[0048] It should be understood that the plasma processing device is a device used to generate and maintain a low-temperature plasma environment for physical or chemical modification of the substrate film surface. For example, in this embodiment of the invention, the plasma processing device employs a capacitively coupled plasma etching machine. The vacuuming process is an operation that extracts the gas inside the plasma processing device, reducing the pressure within the processing chamber. Its function is to remove air impurities, create a pure environment for subsequent argon gas introduction, and ensure controllable plasma composition. The processing chamber is the space within the plasma processing device used to contain the dried substrate film and conduct the plasma reaction. It is a sealed container, and its function is to provide a closed plasma reaction environment to prevent external contamination. The activation time is the duration of argon gas introduction and radio frequency power application during the plasma surface activation process. The length of the activation time directly affects the surface free energy of the activated substrate film. The basis for setting multiple activation times is that different dried substrate films have different initial surface states. By setting multiple activation times, the shortest activation time required for the surface free energy to reach the threshold can be found. The activation environment is a gaseous environment formed by argon gas and the subsequently applied radio frequency electric field after argon gas is introduced into the processing chamber and maintained at a certain pressure. Its function is to serve as the gas source of plasma. Argon gas is ionized under the action of radio frequency electric field to generate argon ions, electrons and active particles, which bombard the surface of the base film.

[0049] It should be clarified that the plasma surface activation treatment is a process in which argon gas is excited in a processing chamber to generate plasma. The plasma bombards the surface of the dried base film, causing the chemical bonds on the surface to break and introducing polar functional groups such as hydroxyl and carboxyl groups. Its function is to increase the surface free energy of the dried base film and enhance its adhesion to the subsequent modified layer. The activated base film is an intermediate product obtained after the dried base film undergoes plasma surface activation treatment. Its surface has partially introduced polar functional groups, but the surface free energy requirement has not yet been met. The surface contact angle test is an operation to measure the static contact angle of a water droplet on the surface of the activated base film. Its function is to quantitatively evaluate the hydrophilicity of the activated base film surface; a smaller contact angle indicates better hydrophilicity. The specific process of the surface contact angle test is as follows: the activated base film is placed horizontally, a preset volume (e.g., 2 μL) of water is added, and the contact angle value is measured at a preset time point (e.g., 0.1 s) after the water droplet falls. The activated contact angle parameter is the angle value directly output from the surface contact angle test, in degrees (°), representing the angle formed between the water droplet and the activated substrate film surface, used for subsequent calculation of surface free energy. The surface free energy is a physical quantity characterizing the wettability of the activated substrate film surface, in millinewtons per meter (mN / m). The higher the surface free energy, the stronger the hydrophilicity. The surface tension of the liquid is an artificially set surface tension constant of the test liquid, measured in millinewtons per meter (mN / m). For example, in this embodiment of the invention, deionized water is used as the test liquid, and its surface tension at 20°C is [missing value]. The surface free energy threshold is the lower limit value used to determine whether plasma surface activation treatment is qualified, and its unit is millinewtons per meter. The setting is based on: when the surface free energy reaches... When the above conditions are met, the adhesion between the subsequently coated modified layer and the base film satisfies the usage requirements; therefore, the surface free energy threshold is set to [value missing]. If the calculated surface free energy is less than This indicates insufficient activation.

[0050] Specifically, the standard composite membrane is obtained by sequentially spinning, crosslinking, coating, and curing a standard base membrane using a composite membrane fabrication system, spinning solution, and modifying solution, including: A standard base film is fixed onto a receiving roller to obtain a fixed base; The spinning solution is injected into a syringe, and the fixed substrate is electrospinned using the syringe to obtain a spun composite film. The spun composite membrane is placed in a crosslinking device, and pre-prepared ethylenediamine vapor is introduced into the crosslinking device for crosslinking treatment to obtain a crosslinked composite membrane. The cross-linked composite membrane is placed in a coating device, and the cross-linked composite membrane is filtered and coated with a modified liquid to obtain a precursor membrane. The precursor film is placed in a curing device for segmented curing to obtain a standard composite film.

[0051] Understandably, the fixed substrate is an integral structure formed by flattening and fixing the standard base film onto the surface of the receiving roller. The rotation of the receiving roller drives the fixed substrate to rotate, allowing the fibers generated by subsequent electrospinning to be uniformly deposited on the surface of the standard base film. The electrospinning process involves using a syringe to stretch the spinning solution into nanoscale fibers under a high-voltage electric field and depositing them onto the surface of the fixed substrate. Its function is to form a uniform polyetherimide fiber layer on the surface of the standard base film. The electrospinning process is existing technology, and its specific details will not be elaborated further. The spun composite film is an intermediate product obtained after electrospinning the standard base film. Its surface is covered with a polyetherimide fiber layer, which serves as the reaction substrate for subsequent crosslinking treatment and also enhances the mechanical strength of the composite film.

[0052] It should be understood that the crosslinking treatment involves placing the spun composite membrane in a crosslinking device and introducing ethylenediamine vapor, causing the imine bonds in the polyetherimide fiber layer to undergo a ring-opening crosslinking reaction with ethylenediamine. Its function is to improve the mechanical stability and solvent resistance of the polyetherimide fiber layer, transforming the linear polyetherimide molecules into a three-dimensional network structure, forming a stable crosslinked layer. This crosslinking treatment process is existing technology, and its specific steps will not be elaborated further. The crosslinked composite membrane is an intermediate product obtained after the crosslinking treatment of the spun composite membrane. Its polyetherimide fiber layer has been transformed into a crosslinked network structure, enhancing its adhesion to the base membrane and providing a stable intermediate transition layer for subsequent coating. The filtration coating treatment involves passing the modified liquid through the crosslinked composite membrane via filtration, allowing the graphene oxide and carbon nanotubes in the modified liquid to be loaded onto the surface of the crosslinked composite membrane. Its function is to form a uniform and dense composite modified layer on the surface of the crosslinked layer, imparting antifouling properties to the crosslinked composite membrane. This filtration coating treatment is existing technology, and its specific steps will not be elaborated further. The precursor membrane is an intermediate product obtained by filtration and coating of a cross-linked composite membrane. Its surface has been loaded with a composite modified layer formed by graphene oxide and carbon nanotubes. However, the bond between the modified layer and the base membrane is not yet strong and further curing treatment is required to eliminate internal stress and enhance the bonding force.

[0053] Specifically, the step of placing the precursor film in a curing device for segmented curing to obtain a standard composite film includes: Measure the initial dimensional parameters of the precursor membrane, including the initial length and initial width; Set multiple curing conditions, each of which includes curing temperature and curing time; Curing conditions are extracted sequentially from multiple sets of curing conditions. The curing device is initialized using the curing temperature and curing time in the curing conditions. The precursor film is then cured using the initialized curing device to obtain the cured film. Measure the cured dimensional parameters of the film, including the cured length and cured width. The isotropic shrinkage rate was calculated based on the initial and cured dimensional parameters, using the following formula:

[0054] in, This represents the isotropic shrinkage rate. This indicates the initial length. This indicates the length after curing. This represents the initial width. Indicates the width after curing; When the isotropic shrinkage rate is not greater than the preset shrinkage rate threshold, the cured film is used as the standard composite film.

[0055] It should be clarified that the initial size parameters are the set of geometric dimensions of the precursor film measured before curing, including the initial length and initial width. Their purpose is to serve as a benchmark for calculating the dimensional shrinkage rate after curing and to evaluate the dimensional stability of the film material during the curing process. The initial length is the original dimension of the precursor film in the length direction, in millimeters (mm). The initial width is the original dimension of the precursor film in the width direction, in millimeters (mm). The curing conditions are a set of parameters used to control the segmented curing process. Each set of curing conditions includes a curing temperature and a curing time. The purpose of setting multiple sets of curing conditions is to try different combinations of temperature and time in turn to find the optimal curing conditions that allow the cured film shrinkage rate to meet the requirements. The number and specific values ​​of the curing conditions are determined based on preliminary experiments. For example, the first set: curing temperature 80℃, curing time 30min; the second set: curing temperature 100℃, curing time 40min; the third set: curing temperature 120℃, curing time 50min. The curing temperature is the heating temperature set inside the curing device, in degrees Celsius (°C). The curing time is the time required for the precursor film to cure at the curing temperature, measured in minutes (min). The curing temperature and curing time together affect the degree of curing and determine the thermal shrinkage characteristics of the film material. The curing process involves placing the precursor film in a curing device and heating it at the set curing temperature and time to ensure a firm bond between the modified layer and the base film and to eliminate internal stress. The cured film is an intermediate product obtained after a set of curing processes on the precursor film. If the shrinkage rate meets the requirements, the cured film is output as a standard composite film; otherwise, it is cured again under the next set of curing conditions.

[0056] It should be explained that the post-curing dimensional parameters are a set of geometric dimensions measured after the curing process, including the post-curing length and width. Their purpose is to compare them with the initial dimensional parameters to calculate the shrinkage rate. The post-curing length is the length dimension of the cured film, in millimeters (mm). The post-curing width is the width dimension of the cured film, in millimeters (mm). The isotropic shrinkage rate is a comprehensive index quantifying the degree of shrinkage of the cured film in both length and width directions. It is a dimensionless parameter; the smaller the isotropic shrinkage rate, the smaller the dimensional change of the film during curing, the less anisotropic deformation, and the better the quality of the cured film. The shrinkage rate threshold is a critical value used to determine whether the dimensional stability of the cured film is acceptable. It is also a dimensionless parameter. The shrinkage rate threshold is set based on the upper limit of the isotropic shrinkage rate of a composite film that meets the requirements, determined through preliminary experiments. For example, in this embodiment of the invention, the shrinkage rate threshold is set to 0.05. When the isotropic shrinkage rate is not greater than 0.05, the curing process is considered acceptable, and the film does not exhibit obvious warping or deformation; otherwise, it is considered unacceptable.

[0057] S5. Conduct antifouling performance tests on standard composite membranes to obtain antifouling performance datasets. Summarize the antifouling performance datasets to obtain k antifouling performance datasets.

[0058] Understandably, the antifouling performance test is a set of experimental procedures used to evaluate the antifouling performance of a standard composite membrane, including: static water contact angle test, pure water flux test, oil-water emulsion rejection rate test, continuous filtration flux decay rate test, and flux recovery rate test after cleaning. The specific test procedures are all existing technologies and will not be elaborated here. The antifouling performance dataset is a collection of multiple parameter values ​​obtained after a single standard composite membrane has completed all the above tests, including: static water contact angle parameter, pure water flux parameter, oil-water rejection rate parameter, flux decay rate parameter, and flux recovery rate parameter. The purpose of the antifouling performance dataset is to comprehensively characterize the antifouling performance of a standard composite membrane, providing data for subsequent selection of the optimal composite membrane.

[0059] S6. Select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k.

[0060] It should be understood that the qualified anti-pollution dataset is a qualified anti-pollution performance dataset.

[0061] Specifically, the step of selecting n qualified anti-pollution datasets from k anti-pollution performance datasets includes: Anti-fouling performance datasets are extracted sequentially from k anti-fouling performance datasets, wherein the anti-fouling performance datasets include: static water contact angle parameters, pure water flux parameters, flux decay rate parameters, flux recovery rate parameters, and oil-water retention rate parameters. Obtain a set of antifouling performance thresholds, which includes: static water contact angle threshold, pure water flux threshold, flux decay rate threshold, flux recovery rate threshold, and oil-water retention rate threshold. If the static water contact angle parameter is not greater than the static water contact angle threshold, the pure water flux parameter is not less than the pure water flux threshold, the flux decay rate parameter is not greater than the flux decay rate threshold, the flux recovery rate parameter is not less than the flux recovery rate threshold, and the oil-water retention rate parameter is not less than the oil-water retention rate threshold, then the corresponding anti-fouling performance dataset is determined to be a qualified anti-fouling dataset. By summarizing the qualified anti-fouling datasets, n qualified anti-fouling datasets are obtained.

[0062] It should be clarified that the static water contact angle parameter is the measured angle between the membrane surface and the water droplet surface at the contact point where the membrane surface, water droplet, and air meet after a deionized water droplet is dropped onto the surface of the standard composite membrane and the droplet reaches equilibrium. The unit is degrees (°), reflecting the hydrophilicity of the standard composite membrane surface; a smaller static water contact angle indicates better hydrophilicity. The pure water flux parameter is the volume of pure water that permeates through the standard composite membrane per unit pressure and unit time, measured in liters per square meter per hour. The parameters reflect the permeation efficiency of the standard composite membrane. The flux decay rate parameter is the percentage decrease in flux of the standard composite membrane during continuous filtration of contaminants; it is a dimensionless parameter, and a smaller flux decay rate indicates stronger antifouling ability. The flux recovery rate parameter is the percentage of flux recovery of the standard composite membrane after cleaning; it is a dimensionless parameter, and a larger flux recovery rate indicates better washability and less irreversible fouling. The oil-water rejection rate parameter is the percentage of oil droplets retained by the standard composite membrane in an oil-water emulsion; it is a dimensionless parameter, and a larger oil-water rejection rate indicates better separation performance. The antifouling performance threshold set is a set of manually set critical values ​​used to determine whether each parameter in the antifouling performance dataset is qualified, including: static water contact angle threshold, pure water flux threshold, flux decay rate threshold, flux recovery rate threshold, and oil-water rejection rate threshold.

[0063] It should be explained that the static water contact angle threshold is a critical angle value used to determine whether the hydrophilicity of the standard composite membrane surface is qualified, and the unit is degrees (°). The static water contact angle threshold is set according to the hydrophilicity requirements of ultrafiltration membranes used for treating oily wastewater. When the static water contact angle is not greater than 60°, the membrane surface has good hydrophilicity and antifouling ability. For example, in this embodiment of the invention, referring to the performance indicators of conventional PVDF modified membranes, the static water contact angle threshold is set to 60°. The pure water flux threshold is a critical flux value used to determine whether the permeation efficiency of the standard composite membrane is qualified, and the unit is liters per square meter per hour. The pure water flux threshold is determined based on the treatment efficiency requirements of the target application scenario. For example, through preliminary experimental calculations on the treatment of oily wastewater, when the pure water flux is not lower than... At that time, the standard composite membrane showed better treatment efficiency, therefore the pure water flux threshold was set to [value missing]. The flux decay rate threshold is a dimensionless parameter used to determine whether the antifouling ability of the standard composite membrane is qualified. It is set based on the following: through continuous filtration experiments on multiple batches of standard composite membranes, the flux decay distribution of compliant standard composite membranes was statistically analyzed. The flux decay rates of all compliant membranes were below 30%, so 30% was taken as the flux decay rate threshold. When the flux decay rate is not greater than the threshold, the standard composite membrane can maintain stable operation during continuous filtration. The flux recovery rate threshold is a dimensionless parameter used to determine whether the cleaning and regeneration ability of the standard composite membrane is qualified. It is set based on the following: through cleaning and regeneration experiments, it was determined that when the flux recovery rate is not less than 80%, the standard composite membrane can meet the lifespan requirement of at least 5 operation-cleaning cycles. Therefore, in this embodiment of the invention, the flux recovery rate threshold is set to 80%. The oil-water rejection rate threshold is a dimensionless parameter used to determine whether the separation performance of the standard composite membrane is qualified. The setting is based on the environmental emission standards. For example, in the process of treating oily wastewater, under the condition of oil content of 200mg / L, the oil-water retention rate must be no less than 95% to meet the emission requirements. Therefore, in this embodiment of the invention, the oil-water retention rate threshold is set to 95%.

[0064] S7. Calculate the comprehensive evaluation score of each of the n qualified anti-pollution datasets to obtain n comprehensive evaluation scores. Select the largest comprehensive evaluation score from the n comprehensive evaluation scores and use the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-pollution composite membrane to achieve process optimization of the anti-pollution composite membrane.

[0065] Understandably, the comprehensive evaluation score is a single value obtained by weighted summation of various parameters in the qualified antifouling dataset. It is used to quantitatively evaluate the comprehensive performance of the standard composite membrane. The higher the comprehensive evaluation score, the better the overall performance of the standard composite membrane in multiple dimensions such as hydrophilicity, permeability, antifouling ability, cleaning and regeneration ability, and separation performance. The antifouling composite membrane is the best one selected from n qualified standard composite membranes, that is, the standard composite membrane with the highest comprehensive evaluation score. It is the best composite membrane product obtained after complete process parameter setting, preparation of multiple sets of samples, performance testing, threshold screening, and comprehensive scoring.

[0066] Specifically, the antifouling composite membrane includes: a base membrane, a crosslinking layer, and a composite modification layer. The base membrane is a polyvinylidene fluoride fiber membrane. The crosslinking layer is a polyetherimide fiber layer formed on the surface of the base membrane, shaped by electrospinning and crosslinking of polyetherimide. The composite modification layer is coated on the surface of the crosslinking layer and is formed by a filtration coating method and segmented curing treatment of graphene oxide and carbon nanotubes. The outer diameter of the carbon nanotubes is 30 nm to 50 nm, and the loading of carbon nanotubes in the composite modification layer is [missing information]. The dispersion solvent for the carbon nanotubes and graphene oxide is a 50% (v / v) aqueous ethanol solution.

[0067] It should be understood that the crosslinked layer is a fiber layer formed on the surface of the base film by electrospinning and crosslinking of polyetherimide. Its function is to enhance the overall strength of the composite film and provide an adhesion substrate for the composite modified layer. The composite modified layer is coated on the surface of the crosslinked layer and is formed by a filter coating method and segmented curing treatment of graphene oxide and carbon nanotubes. Its function is to inhibit the adhesion of pollutants through electrostatic repulsion and size exclusion. The outer diameter of the carbon nanotubes refers to the diameter between the outer sides of the carbon nanotube walls, and the unit is nanometers (nm). The loading of carbon nanotubes in the composite modified layer refers to the mass of carbon nanotubes per unit film area, and the unit is grams per square meter. It is used to characterize the balance between anti-pollution performance and flux efficiency.

[0068] Specifically, the calculation of the comprehensive evaluation score for each of the n qualified anti-pollution datasets yields n comprehensive evaluation scores, including: An evaluation weighting system is established, which includes: static water contact angle weight, pure water flux weight, flux decay rate weight, flux recovery rate weight, and oil-water retention rate weight. For each of the n qualified anti-pollution datasets, perform the following operation: The comprehensive evaluation score is calculated based on the evaluation weighting system, the qualified anti-pollution dataset, and the anti-pollution performance threshold set. The calculation formula is as follows:

[0069] in, This represents the overall evaluation score. This represents the static water contact angle weight. This represents the static water contact angle threshold. This represents the static water contact angle parameter. This indicates the pure water flux weight. This represents the pure water flux parameter. This represents the flux decay rate weight. This represents the flux decay rate threshold. This represents the flux attenuation rate parameter. This represents the flux recovery rate weight. This represents the flux recovery rate parameter. This indicates the weight of the oil-water retention rate. This represents the oil-water retention rate parameter.

[0070] It should be clarified that the evaluation weighting system is a set of coefficients that artificially assign relative importance to each parameter in the qualified anti-pollution dataset. These coefficients include: static water contact angle weight, pure water flux weight, flux decay rate weight, flux recovery rate weight, and oil-water retention rate weight. Each weight's value ranges from 0 to 1, and the sum of all weights equals 1. The purpose of the evaluation weighting system is to reflect the degree of emphasis placed on each parameter in the qualified anti-pollution dataset under different application scenarios. For example, when treating oily wastewater, if anti-pollution capability is more important, the flux decay rate and flux recovery rate weights can be set higher; if water quality is more important, the oil-water retention rate weight can be set higher. The static water contact angle weight is the contribution coefficient of the static water contact angle parameter to the comprehensive evaluation score; the smaller the static water contact angle, the higher the comprehensive evaluation score. The pure water flux weight is the contribution coefficient of the pure water flux parameter to the comprehensive evaluation score; the higher the pure water flux, the higher the comprehensive evaluation score. The flux decay rate weight is the contribution coefficient of the flux decay rate parameter in the comprehensive evaluation score; the smaller the flux decay rate, the higher the comprehensive evaluation score. The flux recovery rate weight is the contribution coefficient of the flux recovery rate parameter in the comprehensive evaluation score; the larger the flux recovery rate, the higher the comprehensive evaluation score. The oil-water rejection rate weight is the contribution coefficient of the oil-water rejection rate parameter in the comprehensive evaluation score; the larger the oil-water rejection rate, the higher the comprehensive evaluation score. The weights for static water contact angle, pure water flux, flux decay rate, flux recovery rate, and oil-water rejection rate are set based on the importance that the target application scenario places on the performance represented by each parameter in the qualified anti-fouling dataset.

[0071] To address the problems described in the background section, this invention first identifies the target application scenario and determines the composite membrane fabrication system and basic composite membrane materials based on the target application scenario. The composite membrane fabrication system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, an organic solvent, polyetherimide, graphene oxide, and carbon nanotubes. This invention considers the differences in membrane performance requirements across different application scenarios. Using uniform materials and processes would be difficult to adapt to specific working conditions. Therefore, by clarifying the preparation direction through the target application scenario, a basis is provided for the targeted setting of subsequent process parameters. Secondly, this invention sets k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic materials of the composite membrane, k spinning solutions and k modification solutions are prepared. It can be seen that this invention takes into account the problem that traditional single-factor experiments are inefficient and difficult to cover the space of multiple parameter combinations. Therefore, through the parallel design of multiple process parameter groups, the simultaneous evaluation of multiple formulations and multiple process conditions is achieved. Then, the present invention performs the following operations on each of the k base membranes: using the base membrane, the spinning solution and the modifying solution are extracted from k sets of spinning solutions and k sets of modifying solutions, respectively, and the base membrane is pretreated to obtain a standard base membrane. According to the composite membrane fabrication system, the spinning solution, and the modifying solution, the standard base membrane is sequentially spun, crosslinked, coated, and cured to obtain a standard composite membrane. It is evident that the present invention addresses the problem of isolated testing of various factors and difficulty in systematic comparison in traditional optimization methods. Therefore, through the one-to-one correspondence between the base membrane, spinning solution, and modifying solution, parallel preparation and systematic processing of multiple sets of experiments are achieved. Next, the present invention conducts antifouling performance tests on the standard composite membranes to obtain an antifouling performance dataset. The antifouling performance datasets are then summarized to obtain k antifouling performance datasets. It is evident that the present invention addresses the problem that traditional methods evaluate membrane performance using only a single index, which cannot comprehensively reflect antifouling ability. Therefore, through multi-dimensional antifouling performance testing, complete performance indicators for each membrane sample are obtained. Subsequently, this invention selects n qualified antifouling datasets from k antifouling performance datasets, where n is no greater than k. It is evident that this invention considers that the performance of membranes prepared by some process combinations may not meet the basic application requirements, and directly including them in the evaluation would affect the accuracy of the selection. Therefore, unqualified samples are eliminated through threshold screening to ensure that all data participating in the comprehensive evaluation meet the basic performance standards.Finally, this invention calculates the comprehensive evaluation score for each of the n qualified antifouling datasets, obtaining n comprehensive evaluation scores. The highest comprehensive evaluation score is selected from these n scores, and the standard composite membrane corresponding to this highest score is chosen as the antifouling composite membrane. This optimizes the antifouling composite membrane process. It is evident that this invention addresses the subjectivity and inefficiency of manually comparing multi-dimensional performance data based on experience. By using weighted comprehensive evaluation, multi-dimensional indicators are quantified into a single score, achieving objective and efficient optimal decision-making. Therefore, this invention can efficiently optimize the antifouling composite membrane preparation process, improve the antifouling performance and preparation efficiency of membrane products, and adapt to the needs of different water treatment application scenarios.

[0072] like Figure 2 The diagram shown is a functional block diagram of an antifouling composite membrane and its process optimization system provided in an embodiment of the present invention.

[0073] The antifouling composite membrane and its process optimization system 100 described in this invention can be installed in an electronic device. Depending on the functions implemented, the antifouling composite membrane and its process optimization system 100 may include a scenario system verification module 101, a parameter liquid preparation module 102, a membrane preparation and testing module 103, and a comprehensive evaluation and selection module 104. The module described in this invention can also be called a unit, which is a series of computer program segments that can be executed by the processor of an electronic device and can perform a fixed function, and is stored in the memory of the electronic device. The scenario system confirmation module 101 is used to confirm the target application scenario and determine the composite membrane manufacturing system and the basic materials of the composite membrane based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device and a curing device. The spinning device includes a receiving roller and a syringe. The basic materials of the composite membrane include k base films, organic solvents, polyetherimide, graphene oxide and carbon nanotubes. The parameter liquid preparation module 102 is used to set k process parameter groups, wherein each process parameter group includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount and dispersion time, and k spinning solutions and k modification solutions are prepared according to the k process parameter groups and the basic material of the composite membrane. The membrane preparation and testing module 103 is used to perform the following operations on each of the k base membranes: using the base membrane, extract the spinning solution and the modifying solution from the k sets of spinning solutions and the k sets of modifying solutions respectively, pretreat the base membrane to obtain a standard base membrane, and sequentially perform spinning, crosslinking, coating and curing treatments on the standard base membrane according to the composite membrane manufacturing system, the spinning solution and the modifying solution to obtain a standard composite membrane, perform antifouling performance testing on the standard composite membrane to obtain an antifouling performance dataset, and summarize the antifouling performance datasets to obtain k antifouling performance datasets; The comprehensive evaluation and selection module 104 is used to select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is not greater than k, calculate the comprehensive evaluation score of each qualified anti-pollution dataset in the n qualified anti-pollution datasets to obtain n comprehensive evaluation scores, select the largest comprehensive evaluation score from the n comprehensive evaluation scores, and use the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-pollution composite membrane to achieve process optimization of anti-pollution composite membrane.

[0074] In detail, the modules in the antifouling composite membrane and its process optimization system 100 described in this embodiment of the invention employ the same methods as described above during use. Figure 1 The antifouling composite membrane and its process optimization method described herein use the same technical means and can produce the same technical effect, so they will not be repeated here.

[0075] like Figure 3 The diagram shown is a schematic representation of an electronic device for implementing an anti-fouling composite membrane and its process optimization method according to an embodiment of the present invention.

[0076] The electronic device 1 may include a processor 10, a memory 11 and a bus 12, and may also include a computer program stored in the memory 11 and executable on the processor 10, such as an antifouling composite membrane and its process optimization method program.

[0077] The memory 11 includes at least one type of readable storage medium, such as flash memory, portable hard drive, multimedia card, card-type memory (e.g., SD or DX memory), magnetic memory, disk, optical disk, etc. In some embodiments, the memory 11 can be an internal storage unit of the electronic device 1, such as a portable hard drive. In other embodiments, the memory 11 can be an external storage device of the electronic device 1, such as a plug-in portable hard drive, smart media card (SMC), secure digital card (SD), flash card, etc., equipped on the electronic device 1. Furthermore, the memory 11 includes both internal storage units and external storage devices of the electronic device 1. The memory 11 can be used not only to store application software and various types of data installed on the electronic device 1, such as the code of the anti-fouling composite membrane and its process optimization method program, but also to temporarily store data that has been output or will be output.

[0078] In some embodiments, the processor 10 may be composed of integrated circuits, such as a single packaged integrated circuit or multiple integrated circuits with the same or different functions, including combinations of one or more central processing units (CPUs), microprocessors, digital processing chips, graphics processors, and various control chips. The processor 10 is the control unit of the electronic device, connecting various components of the entire electronic device through various interfaces and lines. It executes programs or modules stored in the memory 11 (e.g., anti-fouling composite film and its process optimization method program), and calls data stored in the memory 11 to perform various functions of the electronic device 1 and process data.

[0079] The bus 12 can be a peripheral component interconnect (PCI) bus or an extended industry standard architecture (EISA) bus, etc. The bus 12 can be divided into an address bus, a data bus, a control bus, etc. The bus 12 is configured to realize the connection and communication between the memory 11 and at least one processor 10, etc.

[0080] Figure 3 Only electronic devices with components are shown; it will be understood by those skilled in the art that... Figure 3 The structure shown does not constitute a limitation on the electronic device 1, and may include fewer or more components than shown, or combine certain components, or have different component arrangements.

[0081] For example, although not shown, the electronic device 1 may also include a power supply (such as a battery) to power the various components. Preferably, the power supply can be logically connected to the at least one processor 10 through a power management device, thereby enabling functions such as charging management, discharging management, and power consumption management. The power supply may also include one or more DC or AC power supplies, recharging devices, power fault detection circuits, power converters or inverters, power status indicators, and other arbitrary components. The electronic device 1 may also include various sensors, Bluetooth modules, Wi-Fi modules, etc., which will not be described in detail here.

[0082] Furthermore, the electronic device 1 may also include a network interface. Optionally, the network interface may include a wired interface and / or a wireless interface (such as a Wi-Fi interface, a Bluetooth interface, etc.), which is typically used to establish communication connections between the electronic device 1 and other electronic devices.

[0083] Optionally, the electronic device 1 may further include a user interface, which may be a display, an input unit (such as a keyboard), and optionally, a standard wired interface or a wireless interface. Optionally, in some embodiments, the display may be an LED display, a liquid crystal display, a touch-sensitive liquid crystal display, or an OLED (Organic Light-Emitting Diode) touchscreen, etc. The display may also be appropriately referred to as a screen or display unit, used to display information processed in the electronic device 1 and to display a visual user interface.

[0084] The program for the anti-fouling composite film and its process optimization method stored in the memory 11 of the electronic device 1 is a combination of multiple instructions. When run in the processor 10, it can achieve the following: The target application scenario is identified, and the composite membrane manufacturing system and basic composite membrane materials are determined based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, organic solvents, polyetherimide, graphene oxide, and carbon nanotubes. Set k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, prepare k spinning solutions and k modification solutions. Perform the following operation on each of the k base films: Using the base membrane, spinning solution and modified solution were extracted from group k spinning solution and group k modified solution, respectively; The base film is pretreated to obtain a standard base film. The standard base film is then spun, crosslinked, coated and cured sequentially according to the composite film manufacturing system, spinning solution and modifying solution to obtain a standard composite film. Antifouling performance tests were conducted on standard composite membranes to obtain antifouling performance datasets. These datasets were then compiled to obtain k antifouling performance datasets. Select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k; Calculate the comprehensive evaluation score of each of the n qualified anti-fouling datasets to obtain n comprehensive evaluation scores. Select the largest comprehensive evaluation score from the n comprehensive evaluation scores and use the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-fouling composite membrane to achieve process optimization of the anti-fouling composite membrane.

[0085] Specifically, the processor 10's implementation method for the above instructions can be found in [reference needed]. Figures 1 to 3 The descriptions of the relevant steps in the corresponding embodiments are not repeated here.

[0086] Furthermore, if the modules / units integrated in the electronic device 1 are implemented as software functional units and sold or used as independent products, they can be stored in a computer-readable storage medium. The computer-readable storage medium can be volatile or non-volatile. For example, the computer-readable medium may include: any entity or device capable of carrying the computer program code, a recording medium, a USB flash drive, a portable hard drive, a magnetic disk, an optical disk, a computer memory, or a read-only memory (ROM).

[0087] The present invention also provides a computer-readable storage medium storing a computer program, which, when executed by a processor of an electronic device, can perform the following: The target application scenario is identified, and the composite membrane manufacturing system and basic composite membrane materials are determined based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, organic solvents, polyetherimide, graphene oxide, and carbon nanotubes. Set k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, prepare k spinning solutions and k modification solutions. Perform the following operation on each of the k base films: Using the base membrane, spinning solution and modified solution were extracted from group k spinning solution and group k modified solution, respectively; The base film is pretreated to obtain a standard base film. The standard base film is then spun, crosslinked, coated and cured sequentially according to the composite film manufacturing system, spinning solution and modifying solution to obtain a standard composite film. Antifouling performance tests were conducted on standard composite membranes to obtain antifouling performance datasets. These datasets were then compiled to obtain k antifouling performance datasets. Select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k; Calculate the comprehensive evaluation score of each of the n qualified anti-fouling datasets to obtain n comprehensive evaluation scores. Select the largest comprehensive evaluation score from the n comprehensive evaluation scores and use the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-fouling composite membrane to achieve process optimization of the anti-fouling composite membrane.

[0088] In the embodiments provided by this invention, it should be understood that the disclosed devices, systems, and methods can be implemented in other ways. For example, the system embodiments described above are merely illustrative, and actual implementations may have other classification methods.

[0089] The modules described as separate components may or may not be physically separate. The components shown as modules may or may not be physical units; that is, they may be located in one place or distributed across multiple network units. Some or all of the modules can be selected to achieve the purpose of this embodiment according to actual needs.

[0090] Furthermore, the functional modules in the various embodiments of the present invention can be integrated into one processing unit, or each unit can exist physically separately, or two or more units can be integrated into one unit. The integrated unit can be implemented in hardware or in the form of hardware plus software functional modules.

[0091] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for optimizing the antifouling composite membrane process, characterized in that, The method includes: The target application scenario is identified, and the composite membrane manufacturing system and basic composite membrane materials are determined based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device, and a curing device. The spinning device includes a receiving roller and a syringe. The basic composite membrane materials include k base films, organic solvents, polyetherimide, graphene oxide, and carbon nanotubes. Set k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, prepare k spinning solutions and k modification solutions. Perform the following operation on each of the k base films: Using the base membrane, spinning solution and modified solution were extracted from group k spinning solution and group k modified solution, respectively; The base film is pretreated to obtain a standard base film. The standard base film is then spun, crosslinked, coated and cured sequentially according to the composite film manufacturing system, spinning solution and modifying solution to obtain a standard composite film. Antifouling performance tests were conducted on standard composite membranes to obtain antifouling performance datasets. These datasets were then compiled to obtain k antifouling performance datasets. Select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k; Calculate the comprehensive evaluation score of each of the n qualified anti-fouling datasets to obtain n comprehensive evaluation scores. Select the largest comprehensive evaluation score from the n comprehensive evaluation scores and use the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-fouling composite membrane to achieve process optimization of the anti-fouling composite membrane.

2. The method for optimizing the antifouling composite membrane process as described in claim 1, characterized in that, The preparation of k sets of spinning solutions and k sets of modified solutions based on k sets of process parameters and composite membrane basic materials includes: Extract the process parameter sets sequentially from the k process parameter sets; Weigh out the corresponding masses of polyetherimide, organic solvent, graphene oxide, and carbon nanotubes based on the amount of polyetherimide, organic solvent, graphene oxide, and carbon nanotubes added. Polyetherimide was added to an organic solvent for degassing treatment to obtain a spinning solution; Prepare the dispersion solvent according to the solvent concentration; Graphene oxide and carbon nanotubes were added to a dispersion solvent to obtain a mixture; The mixture was subjected to fractional dispersion treatment based on the dispersion time to obtain the modified liquid; The spinning solution and the modified solution were summarized separately to obtain k groups of spinning solutions and k groups of modified solutions.

3. The method for optimizing the antifouling composite membrane process as described in claim 2, characterized in that, The step of fractionating and dispersing the mixture according to the dispersion time to obtain the modified liquid includes: The initial aggregate particle size and specific surface area of ​​carbon nanotubes were determined, and the dispersion difficulty coefficient was calculated based on the initial aggregate particle size and specific surface area. Set a first dispersion level threshold and a second dispersion level threshold, wherein the second dispersion level threshold is greater than the first dispersion level threshold; If the dispersion difficulty coefficient is not greater than the first dispersion level threshold, the mixture is ultrasonically dispersed using a preset first ultrasonic power according to the dispersion time to obtain dispersion No.

1. If the dispersion difficulty coefficient is greater than the second dispersion level threshold, the mixture is ultrasonically dispersed using a preset second ultrasonic power according to the dispersion time to obtain dispersion No.

2. Otherwise, the mixture is ultrasonically dispersed using a preset third ultrasonic power according to the dispersion time, and a pre-prepared dispersant is added during the ultrasonic dispersion process to obtain dispersion No.

3. The No. 1 dispersion, No. 2 dispersion, or No. 3 dispersion is used as the modifying liquid.

4. The method for optimizing the antifouling composite membrane process as described in claim 2, characterized in that, The pretreatment of the base film to obtain a standard base film includes: The base film is immersed in a dispersion solvent for wetting treatment to obtain an impregnated base film; The impregnated base film was subjected to ultrasonic cleaning to obtain an ultrasonically cleaned base film. The ultrasonically cleaned base film is dried to obtain a dried base film. The dried base film was subjected to plasma surface activation treatment to obtain an activated base film; The activated base film was subjected to low-temperature plasma surface etching to obtain a standard base film.

5. The method for optimizing the antifouling composite membrane process as described in claim 4, characterized in that, The process of performing plasma surface activation treatment on the dried base film to obtain an activated base film includes: The dried base film was fixed in a pre-constructed plasma processing device and subjected to vacuum treatment to obtain a processing chamber; Multiple activation times are set, and the activation time is extracted sequentially from these multiple activation times. Pre-confirmed argon gas is introduced into the processing chamber according to the activation time to obtain the activation environment. The dried base film was subjected to plasma surface activation treatment in an activation environment to obtain an activated base film; The surface contact angle of the activated base film was tested to obtain the contact angle parameters after activation. The surface free energy of the activated substrate film is calculated based on the contact angle parameters after activation, and the calculation formula is shown below: ; in, This represents the surface free energy. This indicates the preset liquid surface tension. This represents the activated contact angle parameter. This represents the preset cosine function; If the surface free energy is not less than the preset surface free energy threshold, then the activated base film is used as the activated base film.

6. The method for optimizing the antifouling composite membrane process as described in claim 1, characterized in that, The standard composite membrane is obtained by sequentially spinning, crosslinking, coating, and curing a standard base membrane using a composite membrane fabrication system, spinning solution, and modifying solution. The process includes: A standard base film is fixed onto a receiving roller to obtain a fixed base; The spinning solution is injected into a syringe, and the fixed substrate is electrospinned using the syringe to obtain a spun composite film. The spun composite membrane is placed in a crosslinking device, and pre-prepared ethylenediamine vapor is introduced into the crosslinking device for crosslinking treatment to obtain a crosslinked composite membrane. The cross-linked composite membrane is placed in a coating device, and the cross-linked composite membrane is filtered and coated with a modified liquid to obtain a precursor membrane. The precursor film is placed in a curing device for segmented curing to obtain a standard composite film.

7. The method for optimizing the antifouling composite membrane process as described in claim 6, characterized in that, The step of placing the precursor film in a curing device for segmented curing to obtain a standard composite film includes: Measure the initial dimensional parameters of the precursor membrane, including the initial length and initial width; Set multiple curing conditions, each of which includes curing temperature and curing time; Curing conditions are extracted sequentially from multiple sets of curing conditions. The curing device is initialized using the curing temperature and curing time in the curing conditions. The precursor film is then cured using the initialized curing device to obtain the cured film. Measure the cured dimensional parameters of the film, including the cured length and cured width. The isotropic shrinkage rate was calculated based on the initial and cured dimensional parameters, using the following formula: ; in, This represents the isotropic shrinkage rate. This indicates the initial length. This indicates the length after curing. This represents the initial width. Indicates the width after curing; When the isotropic shrinkage rate is not greater than the preset shrinkage rate threshold, the cured film is used as the standard composite film.

8. The method for optimizing the antifouling composite membrane process as described in claim 1, characterized in that, The process of selecting n qualified anti-pollution datasets from k anti-pollution performance datasets includes: Anti-fouling performance datasets are extracted sequentially from k anti-fouling performance datasets, wherein the anti-fouling performance datasets include: static water contact angle parameters, pure water flux parameters, flux decay rate parameters, flux recovery rate parameters, and oil-water retention rate parameters. Obtain a set of antifouling performance thresholds, which includes: static water contact angle threshold, pure water flux threshold, flux decay rate threshold, flux recovery rate threshold, and oil-water retention rate threshold. If the static water contact angle parameter is not greater than the static water contact angle threshold, the pure water flux parameter is not less than the pure water flux threshold, the flux decay rate parameter is not greater than the flux decay rate threshold, the flux recovery rate parameter is not less than the flux recovery rate threshold, and the oil-water retention rate parameter is not less than the oil-water retention rate threshold, then the corresponding anti-fouling performance dataset is determined to be a qualified anti-fouling dataset. By summarizing the qualified anti-fouling datasets, n qualified anti-fouling datasets are obtained.

9. An antifouling composite membrane based on the process optimization method for antifouling composite membranes according to any one of claims 1 to 8, characterized in that, include: The antifouling composite membrane comprises: a base membrane, a crosslinking layer, and a composite modification layer. The base membrane is a polyvinylidene fluoride (PVDF) fiber membrane. The crosslinking layer is a polyetherimide (PEI) fiber layer formed on the surface of the base membrane, shaped by electrospinning and crosslinking of PII. The composite modification layer is coated onto the surface of the crosslinking layer and is formed by a filtration coating method and segmented curing of graphene oxide and carbon nanotubes. The outer diameter of the carbon nanotubes is 30 nm to 50 nm, and the loading of carbon nanotubes in the composite modification layer is [missing information]. The dispersion solvent for the carbon nanotubes and graphene oxide is a 50% (v / v) aqueous ethanol solution.

10. An antifouling composite membrane and its process optimization system, characterized in that, The system includes: The scenario system confirmation module is used to confirm the target application scenario and determine the composite membrane manufacturing system and the basic materials of the composite membrane based on the target application scenario. The composite membrane manufacturing system includes a spinning device, a crosslinking device, a coating device and a curing device, and the spinning device includes a receiving roller and a syringe. The basic materials of the composite membrane include k base films, organic solvents, polyetherimide, graphene oxide and carbon nanotubes. The parameter liquid preparation module is used to set k process parameter groups, each of which includes: polyetherimide addition amount, organic solvent amount, solvent concentration, graphene oxide addition amount, carbon nanotube addition amount, and dispersion time. Based on the k process parameter groups and the basic material of the composite membrane, k spinning solutions and k modification solutions are prepared. The membrane preparation and testing module is used to perform the following operations on each of the k base membranes: using the base membrane, the spinning solution and the modifying solution are extracted from k sets of spinning solutions and k sets of modifying solutions respectively, the base membrane is pretreated to obtain a standard base membrane, the standard base membrane is sequentially spun, crosslinked, coated and cured according to the composite membrane manufacturing system, the spinning solution and the modifying solution to obtain a standard composite membrane, the antifouling performance of the standard composite membrane is tested to obtain an antifouling performance dataset, and the antifouling performance datasets are summarized to obtain k antifouling performance datasets; The comprehensive evaluation and selection module is used to select n qualified anti-pollution datasets from k anti-pollution performance datasets, where n is no greater than k. It calculates the comprehensive evaluation score of each qualified anti-pollution dataset in the n qualified anti-pollution datasets to obtain n comprehensive evaluation scores. It selects the largest comprehensive evaluation score from the n comprehensive evaluation scores and uses the standard composite membrane corresponding to the largest comprehensive evaluation score as the anti-pollution composite membrane to achieve process optimization of anti-pollution composite membrane.